APLIKASI BIOSLURY PADAT TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT PRE NURSERY PADA BERBAGAI JENIS TANAH - Sri Manu Rohmiyati; Pauliz Budi Hastuti; Gilang Raka Mahessa (AGROISTA : Jurnal Agroteknologi, 2018)
The aim of the study was to determine the effect of volume of solid bioslury and soil type on the growth of pre-nursery oil palm seedlings. This research was conducted at the Education and Research Garden, STIPER Agricultural Institute, located in Maguwoharjo, Sleman, Yogyakarta. The experimental design used was a completely randomized design consisting of two factors and four replications. The first factor was the bioslury volume consisting of five levels (0% + chemical fertilizer, 10%, 20%, 30% and 40%) and soil types consisting of three types (regosol, latosol, and grumosol). The data of the research were analyzed with analysis of variance at a real level of 5%. Data that was significantly different was further tested with 5% DMRT (Duncan Multiple Range Test). The results showed that there was no good combination of bioslury volume and soil type on the growth of pre-nursery oil palm seedlings. The 10% bioslury volume has the same effect as bioslury 20% and 40% but is better than 30% volume and chemical fertilizer. The use of regosol and latosol soils has the same and better effect than grumosol soil on the growth of oil palm seedlings in the pre nursery. Kata kunci : bioslury, regosol, latosol, grumosol, palm oil